Reciprocal Peer Teaching Learning Model In Improving Students' Independence and Educational Interaction In Fiqh Lessons - Fiki Amalia Ali; Muhammad Munif (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
his study intends to reveal; (1) What is the urgency of the reciprocal peer teaching learning model in increasing student independence and educational interaction in fiqh learning at MTs Azzainiyah and MTs Darul Hikmah Paiton Probolinggo Misbahul Fata Banyuanyar Probolinggo. (2) How is the application of the reciprocal peer teaching learning model in increasing student independence and educational interaction in fiqh learning at MTs Darul Hikmah. (3) What are the implications of the reciprocal peer teaching learning model in improving student independence and educational interactivity in fiqh learning at MTs Azzainiyah and MTs Darul Hikmah. The model used in this study is qualitative research with a case study approach. Data collection techniques are carried out by interviews, observations, and documentation. In the data analysis, this study uses the Miles & Huberman model analysis procedure, namely using interactive analysis by collecting data, presenting data, reducing data, and drawing conclusions. While checking the validity of the data is carried out by extending the time and persistence of observation, triangulation techniques and discussions with friends. The research findings are as follows; (1) The learning model using Reciprocal Peer Teaching in fiqh lessons in madrasas has several urgencies (2) The application of the Reciprocal Peer Teaching learning model has several steps of application in learning fiqh subjects in madrasas. The following are some of the main roles of the Reciprocal Peer Teaching learning model in the context of fiqh lessons. (3) Using the Reciprocal Peer Teaching learning model has several implications in it.